INTERPERSONAL METADISCOURSE MARKERS AS PERSUASIVE STRATEGIES IN BARACK OBAMA’S 2012 CAMPAIGN SPEECHES - Bayu Permana Sukma (Balai Bahasa Provinsi Bali, 2017)
One of language features which can be applied to reach the persuasive goal is interpersonal metadiscourse. Although it has been frequently investigated in written texts, research on interpersonal metadiscourse in campaign speeches is still relatively hard to find, whereas a lot of features of interpersonal metadiscourse in campaign speeches are used as persuasive strategies. This study aims to explain the meaning of interpersonal metadiscourse markers applied in Barack Obama’s campaign speeches related to his persuasive strategy. The data are analyzed by using Dafouz’s (2008) theory of interpersonal metadiscourse markers categorization. The method used in this study is descriptive qualitative. The results reveal that all interpersonal metadiscourse markers categories, namely hedges, certainty markers, attributors, attitude markers, and commentaries, are used in Barack Obama’s campaign speeches. High frequency of use of attitude markers and commentaries shows that Obama in his campaign speeches tries to build emotional ties with his audience as his persuasive strategy.